Carbon fluxes in soil systems supplemented with glucose and cadmium - S.Y. Selivanovskaya; A.R. Gilmullina; Y.V. Kuzyakov; P.Y. Galitskaya (Учёные записки Казанского университета: Серия Естественные науки)
Carbon fixation in soil, its transformation and mineralization are the important stages of carbon cycle regulating soil fertility and ecosystem stability. Organic fertilizers and toxic substances, such as heavy metals, lead to changes in the natural carbon flux. Organic and soluble organic carbon contents, microbial biomass, and cumulative respiratory activity have been measured for soils influenced by glucose and cadmium addition and sampled from various depths. Soluble organic compounds (here glucose) lead to a strong increase in metabolic activity, but they cause no carbon fixation in soil in the form of microbial biomass or insoluble compounds. The introduction of heavy metals into the soil has reduced the carbon flux rate through the soluble carbon pool, but has left the microbial biomass carbon unaffected. These effects turned out to be more pronounced in subsoils (below 20 cm) having low organic matter content.